2013
DOI: 10.1098/rsbl.2012.0989
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the determinants of insular body size shifts

Abstract: The island rule, a pattern of size shifts on islands, is an oft-cited but little understood phenomenon of evolutionary biology. Here, we explore the evolutionary mechanisms behind the rule in 184 mammal species, testing climatic, ecological and phylogenetic hypotheses in a robust quantitative framework. Our findings confirm the importance of species' ecological traits in determining both the strength and the direction of body size changes on islands. Although the island rule pattern appears relatively weak ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…Although several previous studies examining the island rule have suggested that changes in predation, interspecific competition and population density are responsible for insular body size change (see electronic supplementary material, appendix S1), accurate accounts of island population densities and community composition are not available from primary literature for as broad a sampling of cases as we wished to include. Details on data collection can be found in the electronic supplementary material for McClain et al [11]. As island area and elevation can both be indicators of island terrain heterogeneity [10], we combined measures of the two in a principal components analysis and used PC1 as a measure of island heterogeneity (electronic supplementary material, table S1).…”
Section: Materials and Methods (A) Island Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although several previous studies examining the island rule have suggested that changes in predation, interspecific competition and population density are responsible for insular body size change (see electronic supplementary material, appendix S1), accurate accounts of island population densities and community composition are not available from primary literature for as broad a sampling of cases as we wished to include. Details on data collection can be found in the electronic supplementary material for McClain et al [11]. As island area and elevation can both be indicators of island terrain heterogeneity [10], we combined measures of the two in a principal components analysis and used PC1 as a measure of island heterogeneity (electronic supplementary material, table S1).…”
Section: Materials and Methods (A) Island Data Collectionmentioning
confidence: 99%
“…Records of insular rodent populations were taken from the database of McClain et al [11,23], which is an expansion of the database from Meiri et al [8]. The size ratio for each population was calculated as the mean island body size (either mass or the cube of linear measurements when mass was unavailable [5,8]) divided by that same measure of body size from the closest mainland population (see [8] for description of original dataset).…”
Section: Materials and Methods (A) Island Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Some studies have reported that the bodies and bills of island birds systematically shift in size, reflecting evolution toward a generalist niche in species-poor communities (4)(5)(6)(7)(8). The tendency for island taxa to converge toward intermediate body size after colonizing islands is known as the island rule (4), but this ecogeographic rule has proven to be an inconsistent predictor of evolutionary trends in island bird populations (9)(10)(11)(12).…”
mentioning
confidence: 99%